2020
DOI: 10.1038/s41598-020-58507-4
|View full text |Cite|
|
Sign up to set email alerts
|

A dog oviduct-on-a-chip model of serous tubal intraepithelial carcinoma

Abstract: Ovarian cancer is the fifth cause of cancer-related mortality in women, with an expected 5-year survival rate of only 47%. High-grade serous carcinoma (HGSC), an epithelial cancer phenotype, is the most common malignant ovarian cancer. It is known that the precursors of HGSC originate from secretory epithelial cells within the Fallopian tube, which first develops as serous tubal intraepithelial carcinoma (STIC). Here, we used gene editing by CRISPR-Cas9 to knock out the oncogene p53 in dog oviductal epithelia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 72 publications
(120 reference statements)
0
18
0
Order By: Relevance
“…In our hands, higher aspect-ratio structures typically required longer UV exposures due to shadowing effects. 18 , 19 Some resins, when exposed to long UV exposure or high-temperature treatments (120 °C), tend to bend and change colors, and molds produced in flexible resins became harder. In the latter case, recipes using a longer thermal treatment at a lower temperature should be preferred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our hands, higher aspect-ratio structures typically required longer UV exposures due to shadowing effects. 18 , 19 Some resins, when exposed to long UV exposure or high-temperature treatments (120 °C), tend to bend and change colors, and molds produced in flexible resins became harder. In the latter case, recipes using a longer thermal treatment at a lower temperature should be preferred.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, PDMS strongly adheres to those molds. 12 , 16 , 17 Therefore, SLA molds must be treated, with, for example, UV post-curing, 11 16 , 18 , 19 temperature, 12 , 14 , 17 19 solvents, 11 , 13 , 16 sonication, 11 silanization, 12 , 16 , 17 or a coating 11 , 20 (for an overview, see Supporting Information Table S1). However, all these treatments have been reported for one specific resin.…”
mentioning
confidence: 99%
“…They found that Cas9-induced DSBs lead to a transient, p53-dependent cell cycle arrest at G1 through p53-p21-pRB axis independent of the locus targeted, and inhibition of p53 can improve the HDR efficiency. Furthermore, CRISPR MAX efficiently delivered RNP targeting p53 into dog oviductal epithelia cells cultured in a dynamic microfluidic chip, and successfully created an in vitro model that recapitulated human tubal intraepithelial carcinoma (STIC) 168 . To expand the applications of RNP-mediated genome editing, researchers developed a scaffold-mediated delivery platform for CRISPR/Cas9 genome editing 169 .…”
Section: Materials For Rnp Deliverymentioning
confidence: 99%
“…A promising and holistic approach to create a more biomimetic environment uses organ-on-a-chip technology [24,52] to recreate interactions and communication between gametes and embryos, as well as the female reproductive tract (Figure 2E). Recently, a variety of womb-on-a-chip [53], endometriumon-a-chip [54], and oviduct-on-a-chip models [55,56] have been reported, all comprising a mature and differentiated epithelium grown on a porous membrane separating two fluidic (apical and basolateral/blood) compartments. In particular, bovine embryos produced in an oviduct-on-a-chip, and cultured under continuous perfusion, were found to better resemble their in vivo counterparts at the zygote stage than those generated through classical in vitro fertilization (IVF) [55].…”
Section: Microfluidics For Gamete Development Maturation and Selectionmentioning
confidence: 99%